Parâmetros de qualidade na clarificação da lecitina de soja - Castejon, Letícia Vieira (2015)
Soy lecithin is a complex phospholipid in soybean oil, being called commercial soybean lecithin. Its color is amber, high viscosity, smell and taste characteristic. It is widely used as an emulsifier, has its own characteristics due to physical changes, chemical or production processes. This study aimed to assess physico-chemically clarified soy lecithins, by adding hydrogen peroxide to 35% (v / v), the controlled temperature and agitation. It was considered qualitative aspects and also in color, for later use in UHT whole milk and verification of powder characteristics (wettability and solubility). The clarification step is designed experimentally, using a central composite design, the commercial soybean lecithin without peroxide treatment rheology was analyzed, showing pseudoplastic behavior at 25°C and the Newtonian at 50°C, the composition of fatty acids was higher unsaturated content as chromatographic analysis. Clarification produced lighter than lecithin and commercial lecithin was clarified lecithin selected with higher brightness value (L*) to rheological analysis, which showed the same rheological behavior of commercial lecithin, but with slight increases in apparent viscosity. Reviews staining were performed, showing the effects of temperature under constant stirring rotation time and H2O2 concentration (% w/v) to give more red dyes and yellow, intense tint and tended to yellow. The experimental point was obtained in higher brightness, white color at 50°C was 520 seconds of stirring and addition of 2.3% hydrogen peroxide, 35% (w/v). A color model is designed to predict which color parameters influence on the apparent color, for that were analyzed carotenoids and chlorophyll compounds, coming to the conclusion that other substances, such as brown substances and tocopherols, if certain improve the fit. The evaluation of oxidative quality of clarified lecithins have shown the effects of the design variables on the saponification number of responses, oxidation rate, and acid value of water activity, the results showed that in axial conditions are maintained good oxidation states lipid. The application of more clarified lecithin in milk showed that the color of milk powder became clearer. The best solubility and shorter wettability were obtained for added lecithin concentration equal to 1.0% of the applied mass and the powders micrographs showed that the increase in soy lecithin content leaves the smaller beads and the most granular powder.